Relationship Between Harvesting Efficiency and Filament Morphology in Arthrospira platensis Gomont - Ga-Hyeon Kim; Yeong Jun Lee; Jong-Hee Kwon (Microorganisms)
Arthrospira platensis, a filamentous cyanobacterium, exhibits morphological variability influenced by biotic and abiotic factors. We investigated the effect of sodium ion concentration on filament length, growth, and harvest efficiency. Increasing the sodium concentration from 0.2 M to 0.4 M (using NaHCO3 or Na2CO3) led to a significant increase in filament length, from 0.3393 to 0.7084 mm, and longer filaments had increased auto-flotation efficiency (from 87% to 94%) within 3 h. The linear filaments, obtained via spontaneous morphological conversion, also had increased photosynthetic activity and growth rates compared to coiled filaments, and we speculate this was due to decreased self-shading and increased light penetration. However, linear filaments also had poor auto-flotation efficiency (10% after 24 h) and decreased buoyancy, and this likely limits their survival in natural ecosystems. These findings provide insights into optimizing the cultivation of A. platensis for biomass harvesting.